Yoga and PTSD: Improving Emotion-Regulation - Jennifer N. Ross; Jerrilyn Cambron (Current Overview on Disease and Health Research Vol. 2, 2022)
This narrative review presents a high-level overview of the beneficial properties derived by practicing yoga, the specific physiological challenges associated with post-traumatic stress disorder (PTSD), and the medically significant relationship between yoga, PTSD diagnosis and PTSD symptoms as evidenced by published medical studies. Yoga practice is shown to improve emotion-regulation and decrease avoidance and emotional suppression. Yoga participants with PTSD show an improved ability to manage intense emotions while remaining focused on the present moment. These enhanced capabilities reduce the conditioned fear response, which is considered a crucial development in eliminating post-traumatic stress disorder. The focus of this review is primarily placed on a 10-week randomized control trial, 20-week case-series, and two long-term follow-up studies. These qualitative and quantitative studies specifically evaluate the effects of trauma-sensitive yoga practice on treatment-resistant PTSD. The three quantitative studies vary in treatment length and result in statistically significant outcomes. Special emphasis is placed on yoga practice frequency and duration in relation to the symptoms and diagnosis of treatment-resistant PTSD. Given that traditional treatment models for PTSD have high drop-out rates and can contribute to symptom worsening, the promising results shown by yoga treatment for complex post-traumatic stress disorder are particularly notable and worthy of further research.